The Impact of Audit Quality on forecasting Accurate of future operating cash flows - hassan zalaghi; Amin Amir Bakhtiarvand; saied Ebrahimzadeh (مطالعات تجربی حسابداری مالی, 2017)
In this study, the effect of audit quality on the forecasting accuracy of future operating cash flows among between firms listed in the Tehran Stock Exchange has been investigated. Audit quality has been measured with auditor size, auditor industry specialization and auditor tenure.Similar to some previous researches done in this outline, forecasting accuracy of future operating cash flows have been estimated with using model Barth et al (2001). The results of review firms 97 in the years 2007 to 2014 show that size of audit firm and auditor industry specialization have significant positive relationship at the forecasting accuracy of future operating cash flows, so caused increase its .while there is a significant negative relationship between forecasting accuracy of future operating cash flows and auditor tenure. These findings suggest that audit quality can influence the quality of accounting information and therefore it is effected over forecasting accuracy of future operating cash flows.